A PD-FEM approach for fast solving static failure problems and its engineering application. (1st March 2022) - Zhou, Zongqing; Zhang, Daosheng; Gao, Chenglu; Li, Zhuohui; Li, Minghao; Liu, Guannan
Highlights: A PD-FEM approach for fast solving static failure problems is proposed. Solved by assembling the global matrix and adopting the ADR algorithm. The short-range repulsive force is introduced and the coupling force is redefined. Realizing efficient simulation of excavation process of the underground cavern group. Compared with pure PD, coupling approach greatly improves the calculation efficiency. Abstract: A method of coupling of peridynamics (PD) and finite element method (FEM) for fast solving static failure problems is proposed. It is based on the force coupling method and adopts interface elements to couple the PD and FE subregions. By assembling the global matrix of the coupling model and using the adaptive dynamic relaxation (ADR) method to solve it, the static solution of elasticity and crack growth problems can be obtained quickly. By introducing short-range repulsive force and re-defining the coupling force, it is not only suitable for simulating tensile failure problems, but also suitable for compression failure problems. Through comparative analysis, the accuracy and effectiveness of this approach are verified. And then the method is successfully applied to simulate the excavation process of an underground cavern group, and the simulation of damage and failure process of engineering rock mass under complex tension–compression conditions has been realized. The stability characteristics of the surrounding rock are revealed by analyzing the damage and deformation evolution laws. It provides an effective numerical simulation method for predicting the excavation damage zone (EDZ) distribution characteristics and deformation law of the surrounding rock during the excavation of an underground cavern group. At the same time, compared with pure PD, the calculation efficiency is greatly improved, which is of great significance for the realization of engineering-scale simulation.